Participatory Microbiome Research With Hmong and Karen Communities: Lessons Learned - Pajau Vangay; Nancy Yang; Shannon Pergament; Mary Xiong; Bwei Paw; Rodolfo Batres; Dan Knights; Kathleen A. Culhane-Pera (Journal of Participatory Research Methods)
In this brief report, we share lessons learned from the Immigrant Microbiome Project (IMP), a microbiome research study conducted in partnership with the Hmong and Karen communities in Minnesota. Members of the IMP academic-community research team and community advisory board reflected on the community-based participatory research (CBPR) approach used for the IMP project, which informed these lessons learned. The IMP illustrates how microbiome researchers can utilize CBPR, which can improve the validity of research projects, create respectful partnerships, build trust between community members and researchers, and ensure that research results are returned to the community as actions that can improve health.